2020
DOI: 10.1109/access.2020.2964766
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Pipeline Buckling Detection via Demagnetization and Interior Magnetic Measurement

Abstract: Thermal buckling of subsea pipelines often occurs and seriously threatens pipeline safety. The spherical detector (SD) can realize quasi real-time detection of pipeline buckling owing to its low blockage risk and convenient launch-retrieval deployment. Vertical buckling can be judged by the rolling speed of the SD, while lateral buckling can only be judged by the interior magnetic fields. However, irregular magnetic remanence of the pipeline seriously hinders the magnetic detection of lateral buckling. To agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This method also has some drawbacks that are not related to spiral weld localization, but related to pipeline defect detection. The SD can only detect the existence of spiral weld and girth weld, as well as large deformation and vibration of pipeline [30][31][32], but cannot detect weld defects and local corrosion defects of pipe wall, especially the upper side, left side, and right side which are far away from the SD. This is because that the diameter of the SD is smaller than the diameter of the pipe, the SD cannot contact the pipe wall.…”
Section: Further Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method also has some drawbacks that are not related to spiral weld localization, but related to pipeline defect detection. The SD can only detect the existence of spiral weld and girth weld, as well as large deformation and vibration of pipeline [30][31][32], but cannot detect weld defects and local corrosion defects of pipe wall, especially the upper side, left side, and right side which are far away from the SD. This is because that the diameter of the SD is smaller than the diameter of the pipe, the SD cannot contact the pipe wall.…”
Section: Further Discussionmentioning
confidence: 99%
“…The SD has been used in the detection of magnetic anomalies in pipelines, and can identify girth welds from the measured magnetic signals, but cannot identify spiral welds [30]. Afterwards, the structure of SD was optimized to achieve fixed-axis rotation by adding a tungsten disc as counterweight to improve the quality of detected signals [31][32]. However, the existing SD is still unable to locate the crosspoint of spiral and girth welds.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, because the pipeline is too long and opaque, it is not easy to observe the flow state of the spherical IOP Publishing doi:10.1088/1742-6596/2730/1/012028 2 detector inside the pipeline, and it has become a major problem to analyze the motion and mechanical properties of the detector in the pipeline. It is found that when the Reynolds number Re is in the range of 100 to 350, the wake structure of the sphere is very similar to that of the isolated sphere in free flow when the sphere is rolling forward [10] . Krishnan et al [11] simulated the thermodynamics and hydraulics of the sphere under the constraint of the pipe boundary and studied the influence of the diameter ratio on the drag coefficient and the Nusselt number under the condition of the diameter ratio α < 0.5 and the Reynolds number Re < 500.…”
Section: Introductionmentioning
confidence: 92%